Identifying physiological determinants of 800 m running performance using post-exercise blood lactate kinetics - Watanabe, T.; Inaba, T.; van Rassel, C. R.; MacInnis, M. J.; Kakinoki, K.; Hatta, H. (European Journal of Applied Physiology, 2024)
Purpose The aims of the present study were to investigate blood lactate kinetics following high intensity exercise and identify the physiological determinants of 800 m running performance.